Late Cambrian – Tremadocian faunas and events from Angosto del Moreno Section, Eastern Cordillera, Argentina - Moya, Maria Cristina (2003)
The Santa Victoria Group (SVG, late Upper Cambrian – Caradocian) comprises pre–Ashgillian Ordovician deposits of the Argentinean Eastern Cordillera. The most significant section of the SVG in the western flank of the Eastern Cordillera is located in the Angosto del Moreno area (Figure 1a, b). At this locality, the SVG unconformably overlies the Mesón Group (Cambrian s.l.), and unconformably underlies Cretaceous rocks (Yacoraite Formation). Upper Cambrian to lower Lower Ordovician units are separated from upper Lower to Middle Ordovician units (Parcha and Sepulturas formations) by the Tumbaya unconformity (Figure 2). The Angosto del Moreno Section of the SVG is exceptional in terms of the quality of exposures, continuity of deposits, richness of fossils, and accessibility. Diverse aspects concerning the Ordovician geology of this study area have been discussed by Moya et al. (1994, 1998), Moya and Albanesi (2000), Moya and Monteros (2000), Malanca and Brandán (2000), and Gómez Martínez et al. (2002). Previous data and recent paleontological collections enable a preliminary biostratigraphic scheme (Figure 2) for the Upper Cambrian to Tremadocian units of the SVG. A synthesis of the sequence stratigraphy and depositional environments of these units is given by Buatois et al. (this volume).